Evaluasi Kinerja Organisasi Publik Dengan Menggunakan Pendekatan Balanced Scorecard dan Analytic Network Process - Tunggul, Adi Mora; Isnanto, Rizal; Nurhayati, Oky Dwi (Universitas Diponegoro, 2016)
Balanced scorecard is a strategic business management method that links performance evaluation to vision and strategies using a multidimensional set of financial and nonfinancial performance metrics. This study examined both quantitative data for the proposed Analytic Network Process method. The purpose of this research is to build a model that combines the Balanced Scorecard approach and Analytical Network Process to assist in the performance evaluation of public organizations tax services. Balanced Scorecard concept is applied to determine the hierarchy of the financial perspective, customer perspective, internal business processes, and learning and growth perspective as well as their respective performance indicators of public organizations and then Analytical Network Process used to tolerate vagueness and ambiguity of information and built an information system that is applied to facilitate the performance evaluation process. The study provides recommendations to the management of public organizations regarding the tax service strategy to improve the performance of public organizations.